Pendidikan Kesehatan dengan Permainan Edukasi Monopoli Kesehatan Reproduksi (E-Mon Kespro) pada Remaja di Panti Asuhan Putri Muhammadiyah Tanjung Purwokerto - Reni Purwo Aniarti; Ikhwah Mu’minah; Citra Hadi Kurniati (Warta Pengabdian Andalas, 2023)
Adolescence, as individuals in the age group 10-19 years, is marked by physical, emotional, cognitive, and behavioural changes. Behaviours characteristic of adolescence, such as alcoholism, use of narcotics, smoking, and high-risk sexual behaviour, are associated with risk to sexual and reproductive health. Unwanted pregnancies and sexually transmitted diseases can lead to serious common reproductive health concerns for adolescents. Lack of information is a significant factor behind poor adolescent knowledge, attitudes, and risk behaviours. This activity aims to discover adolescents' knowledge of Monopoly game-based learning on reproductive health. Activity in 42 adolescents undergoing health education monopoly game-based learning on reproductive health in July 2022 at Panti Asuhan Putri Muhammadiyah Tanjung Purwokerto. The questionnaire consisted of characteristic data filled by adolescent students such as age, body mass index, early age of menarche, cycle menstruation, and knowledge of adolescents about sexual and reproductive health before intervention measured. The pre-test results found that 42.86% of knowledge on reproductive health was poor. Innovative health education can be used to improve the sexual health education of adolescents. The methods can potentially contribute socially, particularly in improving sexual health behaviour and adolescent knowledge of sexual and reproductive health problems.